Prior to and in the Course of Covid-19 Pandemic: Exploring Learners’ Experiences of Learning English through Narrative Lens - Kholili, Achmad (Elsya : Journal of English Language Studies, 2021)
The language learning largely took place in the classroom, especially prior to Covid-19 pandemic and that this occurrence resulted in simplicity for the learners to learn and interact with each other because they could directly make in contact with their classmates and their teachers. However, since the pandemic developed in March 2020, all the learning process was subsequently altered into online learning. To date, studies on language learning has been undertaken by the researchers both at intra and international level. Despite the existence of these former studies, little work reports the comprehensive picture of language learning experiences prior to and during Covid-19 pandemic. To fill this lacuna, the current article reports on a narrative inquiry of EFL learners’ experiences of learning English prior to and during Covid-19 pandemic. Drawing upon data from a semi-structured interview with two Indonesian EFL learners of the sixth semester majoring in English education program, the finding indicates that EFL learners have sustained multifaceted learning experiences prior to and during the pandemic. They have gone through face-to-face learning prior to the pandemic, asynchronous learning during the pandemic and hybrid learning experience during the Covid-19 pandemic. This article concludes with suggestions for promoting hybrid learning model in the EFL setting, particularly in a higher education during the Covid-19 pandemic.